UTILIZING CHEESE WHEY AS A KEFIR DRINK: REVIEW - Kurniawan, Kurniawan; Milanda, Tiana (PC IAI Sragen, 2025)
Whey is a by-product of the cheese industry that is rich in lactose, protein, and minerals, but is often considered as waste. The use of whey as a basic ingredient for kefir drinks is an innovative solution that not only reduces environmental impacts but also produces functional food products with high added value. This article reviews the potential of cheese whey as a substrate in kefir fermentation, including the chemical characteristics of whey, the kefir whey production process, the health benefits of the resulting bioactive compounds, and the challenges and prospects for its development. Studies have shown that whey fermentation with kefir culture can produce probiotic drinks with beneficial effects on gastrointestinal health, the immune system, and lipid and glucose metabolism. By optimizing fermentation technology and adding complementary nutrients, whey kefir can be an alternative functional drink that is economical, nutritious, and environmentally friendly